2012
DOI: 10.1111/j.1751-7915.2011.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered nisin derivatives with enhanced activity in complex matrices

Abstract: SummaryNisin A is the best known and most extensively characterized lantibiotic. As it is ribosomally synthesized, bioengineering‐based strategies can be used to generate variants. We have previously demonstrated that bioengineering of the hinge region of nisin A can result in the generation of variants with enhanced anti‐microbial activity against Gram‐positive pathogens. Here we created a larger bank of hinge variant producers and screened for producers that exhibit enhanced bioactivity as assessed by agar‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 25 publications
6
38
1
Order By: Relevance
“…L. lactis strains, L. lactis NZ9700, L. lactis NZ9800-pCI372 Nisin A, L. lactis NZ9800-pCI372 M21A (Field et al, 2008), L. lactis NZ9800–pCI372 AAA (Healy et al, 2013) and L. lactis NZ9800-pCI372 Nisin V (Rouse et al, 2012), were grown on M17 supplemented with 5% glucose (GM17) broth (Oxoid, England) or GM17 agar (GM17 broth substituted with 1.5% w/v agar) at 30°C. Strains were stocked in 40% glycerol and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L. lactis strains, L. lactis NZ9700, L. lactis NZ9800-pCI372 Nisin A, L. lactis NZ9800-pCI372 M21A (Field et al, 2008), L. lactis NZ9800–pCI372 AAA (Healy et al, 2013) and L. lactis NZ9800-pCI372 Nisin V (Rouse et al, 2012), were grown on M17 supplemented with 5% glucose (GM17) broth (Oxoid, England) or GM17 agar (GM17 broth substituted with 1.5% w/v agar) at 30°C. Strains were stocked in 40% glycerol and stored at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…Those derived from lactic acid bacteria (LAB) have gained particular attention with respect to their use in the food industry. One of the most extensively studied bacteriocins is nisin A, a bactericidal lantibiotic produced by some strains of Lactococcus lactis (Rouse et al, 2012; Campion et al, 2013; Healy et al, 2013). It is a 3.5 kDa peptide consisting of 34 amino acids and is a flexible and elongated amphipathic peptide that has the ability to form pores as well as inhibit cell wall biosynthesis (Breukink et al, 1999; Wiedemann et al, 2001; Prudêncio et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nisin has been the focus of bioengineering in order to elucidate the relationship between the structure and function of the molecule, as well as with a view to improving functional properties of the peptide [30]. Bioengineering has been fruitful with respect to the introduction of mutations that have a positive impact on the physico-chemical properties of nisin, including better solubility [31], [32], improved stability [32] and an enhanced ability to diffuse through complex polymers [33]. Initial success with regard to increasing the potency of nisin came with the creation of bioengineered nisin derivatives with superior antimicrobial activity against some non-pathogenic targets [13], [34], [35], [36].…”
Section: Introductionmentioning
confidence: 99%
“…Another region of the nisin peptide, the three amino acid 'hinge' region, is particularly amenable to change and bioengineering of this region has had beneficial consequences [34]. Indeed, Rouse et al [35] created a bank of hinge mutants and found that nisin peptides containing hinges consisting of SVA or NAK (rather than the original NMK) displayed an enhanced ability to diffuse through complex polymers, a trait which enabled the variants to outcompete nisin A controlling L. monocyto genes in commercially produced chocolate milk containing the stabiliser carrageenan. Furthermore, Healy et al [36] used site directed mutagenesis of the hinge region to create a novel bank of nisin derivatives and found that AAK, NAI and SLS had enhanced activity towards some microorganisms.…”
Section: Bacteriocin Engineeringmentioning
confidence: 99%